Impacts of Green Growth Policies on Labour Markets and Wage Income Distribution A General Equilibrium Application to Climate and Energy Policies - Chateau, Jean (OECD Publishing, 2018)
This paper explores the consequences on the labour markets of structural changes induced by decarbonisation policies. These policies are likely going to have consequences on labour-income distribution given i) existing rigidities in the labour markets, and ii) their different impacts on sectors and on job categories. These policies are analysed in a general equilibrium modelling framework, which includes interlinkages between different sectors and regions as well as five different categories of workers
Keywords: Environment